Effect of BAU-Biofungicide and Plant Extracts on Seedling Vigour of Maize - Debnath, M; Sultana, A; Rashid, AQMB (Journal of Environmental Science and Natural Resources, 2013)
An experiment was conducted in Seed Pathology Center, Bangladesh Agricultural University, Mymensingh to determine the efficacy of biocontrol means (BAU-Biofungicide, Garlic extract and Neem extract) and vigour index of seedling for controlling the seedborne fungal diseases of maize. In laboratory experiment, the prevalence of seed-borne fungi associated with maize cultivar cv. BARI Bhutta - 6 were investigated by blotter method. The identified fungi species were A. niger, A. flavus, Fusarium sp., P. oxalicum, C. lunata and R. stolonifer. The test materials were treated with BAU-Biofungicide @ 2.5% of seed weight, neem extract @ 1:2 w/v and 1:3 w/v and garlic extract @ 1:2 w/v and 1:3 w/v to control the pathogens. Significantly, the highest germination (87.%) and the lowest incidence of pathogen (4%) was recorded in BAU-Biofungicide treated seed The maize seeds treated by BAU- Biofungicide also show the higher vigour index (2856) followed by neem extract (1:2) treated seed (2621) after germination. DOI: http://dx.doi.org/10.3329/jesnr.v5i2.14602 J. Environ. Sci. & Natural Resources, 5(2): 59-61 2012